Review of The Debt Sustainability Framework For Market Access Countries. (Policy Papers; Policy Paper ;, 2021)
A careful review has revealed significant scope to modernize and better align the MAC DSA with its objectives and the IMF's lending framework. This note proposes replacing the current framework with a new methodology based on risk assessments at three different horizons. Extensive testing has shown that the proposed framework has much better predictive accuracy than the current one. In addition to predicting sovereign stress, the framework can be used to derive statements about debt stabilization under current policies and about debt sustainability.